KAJIAN PEMBUATAN SIRUP BUAH JAMBLANG DENGAN VARIASI PERBANDINGAN AIR DAN BUAH SERTA KONSENTRASI GULA - NOVI SAFRIANI; YANTI MELDASARI LUBIS; DOVIE SUFRIZAL SUFRIN (Jurnal Sagu, 2016)
The aim of this study was to explore the processing of jamblang (Syzygium cumini) fruit into syrup. Moreover,the effect of water and fruit ratio, and sugar concentration on the characteristics of the syrup was investigated.This study was conducted using a completely randomized design factorial consisting of two factors: the ratioof water and fruit (2: 1, 1: 1, 1: 2) and the concentration of sugar (65%, 75%, 85%). The results showed thatthe best quality of the syrup based on organoleptic tests obtained from the treatment combination of waterand fruit ratio = 1: 1 with a sugar concentration of 65%. After pasteurization, the syrup had a pH value of3.89, total sugar of 88.70%, anthocyanin content of 29,73 mg/100 g, antioxidant activity of 58.74%, vitaminC content of 7,04 mg/100 ml and panelists liked its color, aroma and taste.